CAPITALIZATION OF HUMAN SKILLS AND COMPETENCIES – AN EXPLORATORY MODEL - BOUZIDA, Zahia; MALEK, Nadir; GHOMARI, Souhila (Studia Universitatis Babeș-Bolyai Oeconomica, 2022)
The paper aims to synthesize the lessons learned from the analysis of the ISO 9001 quality management system standard. The objective is twofold: first, to understand the role of human capital in the conduct and success of an innovation project within a company, and secondly, to explain the simultaneous effect of this dynamic on the emergence of innovative behaviors. An exploratory study is established with the personnel of the first ISO certified company in Algeria and the proposed hypotheses are tested by the partial least squares structural equation modeling (PLS-sem) method. Analysis of the results show that by acting on certain mechanisms, these standards can be assimilated to a catalog of data that can be utilized to encourage and promote the construction and development of skills and competencies. The findings allow us to better understand the nature of the relationship that may exist between skills management and the quality approach. JEL classification: L15, M59, P23